SCREENING OF SOME PLANT EXTRACTS FOR THEIR OVIPOSITION DETERRENT PROPERTIES AGAINST THE PULSE BEETLE, CALLOSOBRUCHUS CHINENSIS (L.) - MAHESHWARI, HARISH K.; DWTVEDI, S.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Ten plant extracts in two different solvents (Acetone and Pet-ether) were evaluated for their oviposition deterrent properties against the pulse beetle, Callosobruchus chinensis (L.). Out of the plants tested. Acetone extracts of Cassia occidentalis, Croton bonplandianum and Pet-ether extracts of Verbesina encelioides, Cassia occidentalis were found to be effective in deterring oviposition.